Uso de realidade aumentada com o SACRA: construção e teste do Sistema de Desenvolvimento de Percepção em 3D (SDP3D) para Pessoas com Necessidades Especiais Visuais (PNEV s) - Wataya, Roberto Sussumu (2009)
Blind and visually impaired people are unable to see and appreciate pictorial art because of visual problems, for, as we know, visual language is still the prevailing form of communication in cultural activities. Individuals who bear Special Visual Needs (ISVN) can utilize a 3D perception development system, that allows, through an educational process, the ISVN to be prepared for a new reality, that is, to go from the 2D dimension to the 3D. Such a system would help these individuals to read the world in an imagery rich context. This study aimed at showing that systems based on Augmented Reality (AR) can facilitate ISVN`s inclusion in the world of painting. In order to accomplish this study, a Colaborative Authorship with Augmented Reality System (CAARS) was used to develop perception systems. These perception systems were utilized in 3D learning situations with 10 congenital blind adults, 4 of which are undergraduate students at UNASP/SP and 6 graduated professionals. These experiences showed that the proposed perception system offered the congenital blind individuals the possibility of learning all the techniques and concepts of 3D representation and interact with certain autonomy in the environment. The 3D perception systems developed for the congenital blind individuals enables them to have access to museums and other cultural spaces, resulting in a contribution to the social inclusion of this group